Cancer-selective nanoparticles for combinatorial siRNA delivery to primary human GBM in vitro and in vivo. (July 2019) - Kozielski, Kristen L.; Ruiz-Valls, Alejandro; Tzeng, Stephany Y.; Guerrero-Cázares, Hugo; Rui, Yuan; Li, Yuxin; Vaughan, Hannah J.; Gionet-Gonzales, Marissa; Vantucci, Casey; Kim, Jayoung; Schiapparelli, Paula; Al-Kharboosh, Rawan; et al.
Abstract: Novel treatments for glioblastoma (GBM) are urgently needed, particularly those which can simultaneously target GBM cells' ability to grow and migrate. Herein, we describe a synthetic, bioreducible, biodegradable polymer that can package and deliver hundreds of siRNA molecules into a single nanoparticle, facilitating combination therapy against multiple GBM-promoting targets. We demonstrate that siRNA delivery with these polymeric nanoparticles is cancer-selective, thereby avoiding potential side effects in healthy cells. We show that we can deliver siRNAs targeting several anti-GBM genes (Robo1, YAP1, NKCC1, EGFR, and survivin) simultaneously and within the same nanoparticles. Robo1 (roundabout homolog 1) siRNA delivery by biodegradable particles was found to trigger GBM cell death, as did non-viral delivery of NKCC1, EGFR, and survivin siRNA. Most importantly, combining several anti-GBM siRNAs into a nanoparticle formulation leads to high GBM cell death, reduces GBM migration in vitro, and reduces tumor burden over time following intratumoral administration. We show that certain genes, like survivin and EGFR, are important for GBM survival, while NKCC1, is more crucial for cancer cell migration. This represents a powerful platform technology with the potential to serve as a multimodal therapeutic for cancer. Graphical abstract: Bioreducible polymeric nanoparticles encapsulating siRNA combinations are successfully delivered to human glioblastoma cells in vitro and in vivo . The delivered siRNA molecules, including Survivin, EGFR, NKCC1, YAP1, and Robo1, result in tumor cell death, reduced tumor migration in vitro, and reduced tumor burden over time in vivo while avoiding major effects on healthy brain cells.Image 1